فعالية أدوات التهيئة والتعمير في حماية البيئة - عبد الباقي صابر - بن علية محمد (جامعة المسيلة, 2024)
The Algerian legislator has adopted a number of laws related to reconstruction and construction, making all urban activities subject to administrative licenses and certificates, and a series of directives to harmonize the environment with sustainable development considerations and tools to enable the government to carry out its supervisory duties, but despite the importance of these laws, there are many attacks on the environment due to the absence of control over the work of the competent administrative authorities, in contrast to the lack of public awareness of these regulations and their importance in reality.
Keywords: Environmental protection; planning and reconstruction; retail licenses; certificates of conformity.